I'll start with a few definitions: $$\beta \equiv \frac{1}{k_bT}$$

Where T is the temperature of a system.

And the partition function:

$$Z \equiv \sum_{j}e^{-\beta \epsilon_j}=\int D(\epsilon)d\epsilon e^{-\beta\epsilon}$$

Where s is an index over all distinguishable microstates of the system (in the case of discrete states) and $\epsilon$ is the energy of each of the microstates. In the continuous case, $D(\epsilon)$ is the density of states.

So, if we consider the partition function of a photon gas of temperature $T$ where the energy of a photon w/ frequency $\omega$ is $\epsilon = \hbar\omega$, the total energy of an assemblage of photons is given by:

$$E = \sum_i s_i \hbar\omega_i$$

Where i is the index over all possible frequencies $\omega_i$ and $s_i$ is the number of photons with frequency $\omega_i$.

We can then see that the partition function for a photon gas can be expressed as:

$$Z = \sum_{k}e^{-\beta E_k} = \sum_{s_1,s_2,...=0}^{\infty} e^{-\beta\hbar(s_1\omega_1 + s_2\omega_2 +...)} = \sum_{s_1,s_2,...=0}^{\infty} e^{-\beta\hbar s_1\omega_1}e^{ -\beta \hbar s_2\omega_2}...$$

The second equivalence is established by noting that each state $\Psi_k$ is uniquely determined by the number of photons in each mode $M_i$ (each of which has a corresponding frequency $\omega_i$).

$$Z = \sum_{s_1=0}^{\infty}\sum_{s_2=0}^{\infty}... (e^{-\beta\hbar s_1\omega_1}e^{ -\beta \hbar s_2\omega_2}...) = \sum_{s_1=0}^{\infty}e^{-\beta\hbar s_1 \omega_1}\sum_{s_2=0}^{\infty}\sum_{s_3=0}^{\infty}... (e^{-\beta\hbar s_2\omega_2}e^{ -\beta \hbar s_3\omega_3}...)$$

By pulling out the $\omega_1$ term. We can continue this line to arrive at:

$$Z = (\sum_{s_1=0}^{\infty}e^{-\beta\hbar s_1\omega_1})*(\sum_{s_2=0}^{\infty}e^{-\beta\hbar s_2\omega_2})*... = \prod_{i=1}Z_{\omega_i}$$

Where $Z_{\omega}$ is the partition function $\sum_{s=0}^{\infty} e^{-\beta\hbar s \omega}$ for a system consisting of photons only of frequency $\omega$.

However, the partition function of thermal blackbody radiation ends up being very different. For some reason, it is given by:

$$Z = \sum_i Z_{\omega_i} = \int D(\omega) d\omega Z_{\omega}$$

Where $Z_{\omega}$ is the same as defined above. This seems to be a contradiction. So I suppose my question is: Which of these solutions is correct?

  • $\begingroup$ My gut feeling is that you are equivocating (using the same term to mean two different things), and I think that the term you're equivocating over is $s$. We should probably say "state $i$ contains $n_{ij}$ photons at frequency $\omega_j$ leading to $E_i = \sum_j n_{ij} \hbar \omega_j.$ This causes your "derivation" to look instead like $\sum_i \Pi_j \exp(-\beta~n_{ij}~\hbar~\omega_j).$ $\endgroup$ – CR Drost Oct 27 '15 at 2:32
  • $\begingroup$ I tidied up my notation a bit so that there shouldn't be any equivocation. $\endgroup$ – Zane Dufour Oct 27 '15 at 2:59
  • $\begingroup$ Also, I'm not trying to "break" statistical mechanics or something stupid like that. The first result was something I was asked to prove on a homework assignment and the second result was used by my prof to demonstrate the Stefan-Boltzmann law. My assumption is that the two situations are fundamentally different, but I still don't understand why the overall partition function for Blackbody Radiation is a sum instead of a product (it doesn't seem like we're counting states with photons with different frequencies). $\endgroup$ – Zane Dufour Oct 27 '15 at 3:09

In some cases we can approximate the sum by an integral appropriate:

$$\sum_j e^{-\beta\epsilon_j} =\int e^{-\beta E}D(\epsilon)d\epsilon=\int e^{-\beta E(\omega)}D(\omega)d\omega$$

In fact that is how we determine the density function. And I think there is no reason we can write $\sum_i Z_{\omega_i}=\int Z_\omega D(\omega)d\omega$ with the same $D(\omega)$ from the egality above.

And also there is no reason to believe that $Z=\sum_i Z_{\omega_i}$, in fact $Z=\prod_i Z_{\omega_i}$ like you have demonstrated. So that $\ln Z=\sum_i \ln Z_{\omega_i}$, therefore:

$$\ln Z=\int (\ln Z_{\omega_i}) D(\omega)d\omega $$

In fact $D(\omega)d\omega$ counts the number of states having frequency between $\omega$ and $\omega+d\omega$, and similar for $D(\epsilon)d\epsilon$. You can imagine that $$Z=\prod_{\omega_i}Z_{\omega_i}^{D(\omega)d\omega}$$

which mean we have approximate all the frequency in $[\omega,\omega+d\omega]$ by $\omega$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.